Comparison of stage III mucinous and serous ovarian cancer: a case-control study - Zeliha Firat Cuylan; Emine Karabuk; Murat OZ; Ahmet Taner Turan; Mehmet M. Meydanli; Salih Taskin; Mustafa Erkan Sari; Hanifi Sahin; Suat C. Ulukent; Ozgur Akbayir; Kemal Gungorduk; Tayfun Gungor; et al. (BMC, 2018)
Abstract Background The purpose of this case-control study was to compare the prognoses of women with stage III mucinous ovarian carcinoma (MOC) who received maximal or optimal cytoreduction followed by paclitaxel plus carboplatin chemotherapy to those of women with stage III serous epithelial ovarian cancer (EOC) treated in the similar manner. Methods We performed a multicenter, retrospective review to identify patients with stage III MOC at seven gynecologic oncology departments in Turkey. Eighty-one women with MOC were included. Each case was matched to two women with stage III serous EOC in terms of age, tumor grade, substage of disease, and extent of residual disease. Survival estimates were measured using Kaplan-Meier plots. Variables predictive of outcome were analyzed using Cox regression models. Results With a median follow-up of 54 months, the median progression-free survival (PFS) for women with stage III MOC was 18.0 months (95% CI; 13.8-22.1, SE: 2.13) compared to 29.0 months (95% CI; 24.04-33.95, SE: 2.52) in the serous group (p = 0.19). The 5-year overall survival rate of the MOC group was significantly lower than that of the serous EOC group (44.9% vs. 66.3%, respectively; p < 0.001). For the entire cohort, presence of multiple peritoneal implants (Hazard ratio [HR] 2.39; 95% confidence interval [CI], 1.38-4.14, p = 0.002) and mucinous histology (HR 2.28; 95% CI, 1.53-3.40, p < 0.001) were identified as independent predictors of decreased OS. Conclusion Patients with MOC seem to be 2.3 times more likely to die of their tumors when compared to women with serous EOC.